2014
DOI: 10.1111/lam.12326
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous identification by multiplex PCR of major Prototheca spp. isolated from bovine and buffalo intramammary infection and bulk tank

Abstract: This work reports PCR assays based on novel Prototheca spp. mitochondrial and chloroplastic target sequences. The multiplex PCR protocol described in this study is useful for rapid simultaneous detection of P. zopfii, P. wickerhamii and P. blaschkeae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Culture dependent approaches demonstrated that most frequently isolated bacteria during mastitis are coagulase negative, causing 78% of intramammary infections cases of mastitis [ 31 , 32 ], Prototeca spp. and Streptococcus pluranimalium being found occasionally [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Culture dependent approaches demonstrated that most frequently isolated bacteria during mastitis are coagulase negative, causing 78% of intramammary infections cases of mastitis [ 31 , 32 ], Prototeca spp. and Streptococcus pluranimalium being found occasionally [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, pathogenesis of P. bovis, a globally ubiquitous and environmental (grass, water, trees) algae (Rösler et al, 2003) capable of infecting various vertebrate hosts (Seok et al, 2013;Capra et al, 2014;Carfora et al, 2017) remains poorly understood. Therapeutic control for human and animal protothecosis is on demand.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, comprehensive studies focusing on the genotyping of Prototheca species have enabled advancements in the epidemiology of protothecosis among domestic animals, particularly in relation to the geographical distribution of these microalgae (Roesler et al 2006;Ahrholdt et al 2012;Morandi et al 2016). Similar investigations have also reported P. zopfii genotype 2 as the main pathogenic type involved in bovine mastitis globally (M€ oller et al 2007;Jagielski et al 2011;Ahrholdt et al 2012;Capra et al 2014;Morandi et al 2016).…”
Section: Genotypic Characterization Of P Zopfiimentioning
confidence: 93%